Hadith Education in Forming Character of Early Childhood - Muhammad Hambal (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Early childhood is a very brilliant time in the process of character formation, because early age is a time where children absorb a lot of knowledge to be applied in the future. We see the character of the nation's children in this era, the term "Kids of the Age Now" is well known in the public. Examined the origin of the term because of the behavior of children today who are far from the behavior of children should be. Indeed, not all the behavior of children "Kids Zaman Now" has negative implications, when viewed through the eyes of art they have good creativity and mental value. This type of research is library research, namely research whose main object is books or other sources of literature. That is, data are sought and found through literature review from books that are relevant to the discussion. To overcome this incident the role of Islamic education or the inculcation of religious values in daily life can be an alternative in shaping character. Character education is the safeguarding of essential values with learning and assistance so that students as individuals are able to understand, experience, and integrate values that become core values into their personalities. One branch of Islam that can be taught is Hadith. The purpose of teaching hadith in early childhood is to shape and develop good personality and character. Keywords: early childhood, character formation, Hadith,